Monetary Policy and Inflation Targeting in Singapore : A Comparative Study of Pre- and Post-Pandemic Approaches - Kursova, Evgeniia (2025)
The aim of this thesis is to identify and evaluate how Singapore’s monetary policy framework evolved in response to the COVID-19 pandemic. It provides a comparative analysis of the Monetary Authority of Singapore’s (MAS) strategy before and after the pandemic, particularly in the areas of inflation targeting and exchange rate management. The thesis analyses how macroeconomic conditions shaped policy responses and assesses the effectiveness and flexibility of Singapore’s unique exchange rate-centered regime in maintaining price stability and economic resilience. Based on both quantitative data and qualitative evaluation, the author highlights key differences in the scale, timing, and coordination of MAS’ policy tools, offering their own interpretation of MAS’ institutional learning and strategic adaptability. The findings contribute to the broader academic and policy discussion on how small, highly open economies can successfully navigate external shocks and ensure monetary stability under extraordinary circumstances.